Self-efficacy as a predictor of social workers' perceived workload - Katarzyna Nowosad (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
Working in the support professions is associated with a heavy mental and emotional burden. Social workers face human tragedy, difficult situations, a shortage of resources, and the need to make extremely responsible decisions regarding people's fate, and they may even be exposed to aggression from demanding clients. These factors may cause unpleasant experiences and emotional tensions among social workers, disrupting the course and structure of professional activities. Self-efficacy may help in coping with this burden. It constitutes the belief that one has the skills allowing them to cope better with problems (cf. Zientek, 2006; Bandura, 2007; Wierzejska, 2018). The article aims, therefore, to determine the role of self-efficacy in explaining the perceived workload of social workers. The obtained research results indicate that social workers' self-efficacy is a significant predictor of their sense of workload. Keywords: Social worker, workload, self-efficacy Poczucie własnej skuteczności predyktorem odczuwanego obciążenia pracą przez pracowników socjalnych Praca w zawodach pomocowych wiąże się z dużym obciążeniem psychicznym i emocjonalnym. Pracownicy socjalni spotykają się z ludzką tragedią, sytuacjami trudnymi, deficytem środków, koniecznością podejmowania niezwykle odpowiedzialnych decyzji dotyczących ludzkich losów, niekiedy narażeni są nawet na agresję roszczeniowych klientów. Czynniki te mogą powodować przykre przeżycia i napięcia emocjonalne pracowników, zakłócać przebieg i strukturę wykonywanych czynności zawodowych. W radzeniu sobie z tym obciążeniem może pomagać poczucie własnej skuteczności stanowiąc przekonanie, o posiadaniu uzdolnień, które pozwalają lepiej radzić sobie z problemami (por. Zientek, 2006; Bandura, 2007; Wierzejska, 2018). Celem artykułu jest więc określenie roli poczucia własnej skuteczności w wyjaśnieniu odczuwanego obciążenia pracą pracowników socjalnych. Uzyskane wyniki badań wskazują, że poczucie własnej skuteczności pracowników socjalnych stanowi istotny predyktor ich poczucia obciążenia pracą.